Pengaruh diversifikasi dan profitabilitas terhadap nilai perusahaan terdaftar Jakarta Islamic Index 2019-2022 - Prastya, Lutfi Adi; Sari, Indri Juwita; Corlita, Inka (Sekolah Tinggi Ilmu Ekonomi Indonesia (STEI) Jakarta, 2023)
Business is an ongoing effort to make money. According to Molengraaff, a business that wants to make money has an economic perspective. Companies must increase their value if they want to survive in a tight trading climate. Profitability and diversification are two factors that influence company value. To ensure the relationship between two or more variables, associative research techniques with a quantitative approach were used in this research. Eviews 12 is used to process quantitative data. Working theories to describe, predict, and control phenomena were produced by this research. Numbers were used in data collection, data analysis, and presentation of the results of this quantitative study. The 40 businesses registered on the Jakarta Islamic Index form the population, the sample of which has special characteristics. Purposive sampling is the technique used, and the standards used are as follows: (1) Businesses registered on the Jakarta Islamic Index; (2) Businesses included in the 10 Securities Owners with the Largest Ownership in the Jakarta Islamic Index; (3) Companies that present variable data needed in research. Thus, 38 samples of research data were obtained from 40 companies with the 10 largest securities holdings in the Jakarta Islamic Index. This study investigates how profitability and diversification impact firm value. The research objects are companies listed in the Jakarta Islamic Index (JII) for the 2019–2022 period. Based on the results of the discussion, it was found that diversification and profitability had no impact on company value.